FREERTOS BASED AIR QUALITY MONITORING SYSTEM USING SECURE INTERNET OF THINGS - Belen Septian; Md Misbahuddin; Fardhan Arkan (Jurnal Teknik Informatika (Jutif), 2022)
As the number of vehicles is increasing, the air quality in the environment becomes more polluted. This problem happens due to concentration of carbon dioxide (CO2) is high in the air and it can lead to various health issues. The air quality meter is an important device to measure the concentration of CO2 in the air. In this study, an air quality monitoring system is built using Arduino Nano along with IoT technology to measure parameters such as CO2, temperature, humidity, and heat index. FreeRTOS is used to run multiple tasks consisting of display and transmit concurrently. MQ135 and DHT22 are used to sense CO2, temperature, humidity, and heat index respectively. Data will be sent periodically to a web server using ESP8266 Wi-Fi module through secure HTTPS POST protocol. On the back-end side, a web server is employed to receive sensor parameters as well as to build a website application securely by which users can monitor it remotely. The system was tested to monitor CO2 in 4 different locations of Pangkal Pinang city, Indonesia. The results showed that the averages of CO2 concentration in Housing Indo Graha, Morning Market, Dea Lova Park, and Pasir Padi Beach are 411.37 ppm, 485.97 ppm, 416.45 ppm, and 444.43 ppm respectively. Based upon the results, public place i.e. Pasir Padi Beach has higher CO2 concentration meanwhile public place with organic waste i.e. Morning Market has the highest CO2 concentration.